PENERAPAN METODE PENGEMBANGAN LAHAN (LAND DEVELOPMENT ANALYSIS) DALAM PENILAIAN TANAH - Petrus Teguh Subagyo; Nurhidayah (Melati Institute, 2023)
The existence of vacant land in potential locations will provide added value to the owner if the vacant land is optimized. Determining the value of vacant land with an area of 36,640 m2 in a residential area is not possible using the market approach, so the income approach is chosen using the Land Development Analysis method, which is assumed to be developed into a residential area as the best and highest alternative use. Based on the land development plan, the market value of the land is obtained from cash flows originating from sales of housing units minus development costs for the land. From the results of the analysis, an indication of the market value of the land is Rp3.500.891,50.